How does the «Brussels effect» shape new standards? The impact of the GDPR data protection standard and other EU initiatives on Ukraine and countries outside the European Union - Udovenko , Oleksandr; Velychko , Larysa (Pressing Problems of Public Administration, 2024)
This article examines the impact of the European Union’s General Data Protection Regulation (GDPR) on countries beyond the borders of the EU, with a particular focus on Ukraine, through the lens of the «Brussels Effect» concept. The purpose of the article is to unveil the role of the «Brussels Effect» in shaping global standards for personal data protection and its influence on the regulatory adaptation processes of Ukraine and other Eastern Partnership countries to GDPR requirements, based on theoretical and empirical analysis. The methodology employed in this article relies on an eclectic combination of conceptual-theoretical approaches and empirical methods from the arsenal of legal sciences, political analysis, economics, and sociology. This methodological diversity is driven by the need for a holistic understanding of the multidimensional phenomenon of the «Brussels Effect» and its impact on various aspects of personal data regulation. The authors analyze how the GDPR de facto creates a transnational legal regime for personal data protection, compelling third countries to adapt their legislation to European standards. Based on a comparative case study of Ukraine, Georgia, and Moldova, common patterns and specific factors of the harmonization process with GDPR are identified – ranging from the intensity of digital trade with the EU to the political will of national stakeholders. The authors argue that despite the powerful transformative influence of the GDPR, its effective implementation critically depends on the local institutional ecosystem and a cultural revision of attitudes towards privacy. Therefore, full-fledged adaptation to the GDPR requires targeted efforts at all levels – from modernizing legislation to strengthening the capacity of regulators and shaping a proactive stance of citizens. Drawing on a matrix of 6 key dimensions (regulatory framework, institutional model, law enforcement, etc.), practical recommendations are provided for enhancing the extraterritorial effect of the GDPR in the Eastern Partnership region, taking into account the security challenges of hybrid warfare for Ukraine. The article contributes to the current discussion about the EU’s new role as a global regulatory player in the digital age.